Task-irrelevant data impair processing of graph reading tasks: An eye tracking study. (June 2018) - Strobel, Benjamin; Lindner, Marlit Annalena; Saß, Steffani; Köller, Olaf
Abstract: For Instruction, teachers often rely on prefabricated material that may include irrelevant information. However, graphs can place a heavy burden on the cognitive system if their complexity is not suitable for a given task. In this study, we compared bar graphs showing task-irrelevant data points or task-irrelevant data series with a control condition using a within-subject design and eye tracking methodology. Data were analyzed using linear mixed-effects models. Results show that task-irrelevant data significantly elevated processing time, error rate and cognitive load. Even though perceptual grouping by color was expected to aid the process when a task-irrelevant data series was included in a graph, effects were strongest in this condition. Analyses of attention distribution using eye tracking measures revealed that task processing differed qualitatively between the conditions, yielding important implications for instruction. Highlights: We compared two types of task-irrelevant data: data points (DP) and data series (DS). Processing time, error rates and cognitive load were higher in DP and DS items. Effects were larger for task-irrelevant DS than for task-irrelevant DP. Eye-tracking: participants spent more time reading the task text in DS items. Instructors should consider altering graphs to display only task-relevant DS.